2018
DOI: 10.6002/ect.tond-tdtd2017.p27
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Thrombotic microangiopathy is a form of renal capillary injury possibly associated with calcineurin inhibitor toxicity, acute humoral rejection, infections, and recurrent diseases. Here, we examined its incidence in patients diagnosed with acute and chronic active humoral rejection, polyomavirus nephropathy, acute cellular rejection, and immunoglobulin A recurrence. Materials and Methods: In total, 272 renal allograft recipients who met the inclusion criteria were reevaluated for presence of renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(70 reference statements)
0
2
0
2
Order By: Relevance
“…However, the 2-year graft loss rate was similar between the two groups, with nearly 40% in each group. In contrast, another study of 74 individuals with kidney allograft TMA found that those with C4d+ had a higher graft loss rate than those without C4d staining (55.6% vs. 30%) [ 46 ]. Nevertheless, C4d deposits are not uncommon in kidney allograft TMA, particularly in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…However, the 2-year graft loss rate was similar between the two groups, with nearly 40% in each group. In contrast, another study of 74 individuals with kidney allograft TMA found that those with C4d+ had a higher graft loss rate than those without C4d staining (55.6% vs. 30%) [ 46 ]. Nevertheless, C4d deposits are not uncommon in kidney allograft TMA, particularly in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“…La patogenia del MAT se centra en la activación de las células del endotelio vascular, el daño por activación leucocitaria y agregación plaquetaria [6] . Existen diferentes factores desencadenantes que incluyen bacterias, virus, toxinas y drogas (inhibidores de la calcineurina), injuria isquemia-reperfusión, RMA y activación o disregularización del complemento en la aparición del MAT [7][8][9][10] . El caso clínico planteó dos problemas diagnósticos, el primero estuvo centrado en diferenciar si se trataba de una MAT recurrente o de novo.…”
Section: Discussionunclassified
“…El caso clínico planteó dos problemas diagnósticos, el primero estuvo centrado en diferenciar si se trataba de una MAT recurrente o de novo. El SUH recurrente según la literatura se manifiesta con MAT sistémico como es el caso de la paciente y ocurre en el trasplante temprano [9][10][11] , mientras que el MAT secundario es de afectación renal preferentemente y de aparación tardía (después del año), sin embargo, la paciente no tenía ancedente de SUH como causa de su enfermedad renal crónica. Por otro lado, no se pudieron realizar estudios para determinar si se trata de una deficiencia de Dentro de las causas de MAT de novo que se consideraron en la paciente tenemos el RMA, infección por CMV y la toxicidad por tacrolimus [8][9][10][11] .…”
Section: Discussionunclassified
“…The prognosis of de novo or recurrent TMA in kidney allografts is generally guarded and varies according to underlying causes[ 60 - 68 ]. With better understanding and characterization of the disease, the patient and allograft outcomes are improving steadily.…”
Section: Management and Prognosismentioning
confidence: 99%